Conflicting Memory in Estonia: How Do Estonian Russian-speakers Understand the Events of 1939-40? - Forbes-Sarantsin, Annika (My University, 2016)
This thesis studies the collective memory of the Russian-speaking minority living in Estonia. The minority is exposed to two national narratives regarding the incorporation of Estonia into the Soviet Union in 1940. According to the Estonian narrative, Estonia was occupied and annexed by the Soviet Union while the Soviet-Russian narrative sees the actions to have been legal and voluntary. This thesis firstly examines thoughts the existence of these two opposing narratives evoke among the Russian-speaking minority and secondly it explores whether the views of the minority compare with the two official yet divergent narratives. The study focuses on the second and third generation minority members. The topic belongs to the field of memory studies. The objective is to understand the views the Russian minority have towards the controversial events of the years 1939-40. To accomplish the objectives set, a web-based survey using open-ended and multiple-choice questions was conducted. The open-ended questions addressed the main research questions while the multiple-choice questions contributed to forming a more comprehensive understanding of the subject in question. In order to interpret the data, qualitative content analysis has been applied. Based on the findings, the Russian-speaking minority respondents’ understanding of the events of 1939-40 could be described as fragmented, inconsistent and including viewpoints that resulted from the merger of different storylines. There is no single cohesive or coherent narrative of the past amongst the minority. In addition to that, their views do not generally comply with the narrative of the Russian Federation as often referred to in literature, even though the minority respondents do not want to see the Soviet involvement as critically as the Estonian narrative does. Many respondents conceive the events of 1939-40 as ambiguous revealing the ability to be tolerant and receptive in their views regarding the past.